Are wealth transfers biased against girls?: gender differences in land inheritance and schooling investment in Ghana's western region - Quisumbing, Agnes R.; Payongayong, Ellen; Otsuka, Keijiro (International Food Policy Research Institute, 2004)
This study attempts to analyze changing patterns of land transfers and schooling investments by gender over three generations in customary land areas of Ghana's Western Region. Although traditional matrilineal inheritance rules deny landownership rights to women, women have increasingly acquired land through gifts and other means, thereby reducing the gender gap in landownership. The gender gap in schooling has also declined significantly, though it persists. We attribute such changes to the increase in women's bargaining power due to an agricultural technology that increased the demand for women's labor, contributing to the reduction of social" discrimination as well as weak "parental" discrimination." -- Authors' Abstract